You are on page 1of 4

Tarea 1 Ejercicio 10

Reducción de un término que contenga términos semejantes de diversas clases

1 7a − 9b + 6a − 4b =

2 a + b − c − b − c + 2c − a =

3 5 x − 11 y − 9 + 20 x − 1 − y =

4 − 6m + 8n + 5 − m − n − 6m − 11 =

5 − a + b + 2b − 2c + 3a + 2c − 3b =

6 − 81x + 19 y − 30 z + 6 y + 80 x + x − 25 y =

7 15a 2 − 6ab − 8a 2 + 20 − 5ab − 31 + a 2 − ab =

8 − 3a + 4b − 6a + 81b − 114b + 31a − a − b =

9 − 71a 3b − 84a 4 b 2 + 50a 3b + 84a 4b 2 − 45a 3b + 18a 3b =

10 − a + b − c + 8 + 2a + 2b − 19 − 2c − 3a − 3 − 3b + 3c =

11 m 2 + 71mn − 14m 2 − 65mn + m 3 − m 2 − 115m 2 + 6m 3 =

12 x 4 y − x 3 y 2 + x 2 y − 8 x 4 y − x 2 y − 10 + x 3 y 2 − 7 x 3 y 2 − 9 + 21x 4 y − y 3 + 50 =

13 5a x+1 − 3b x + 2 − 8c x +3 − 5a x+1 − 50 + 4b x + 2 − 65 − b x+ 2 + 90 + c x +3 + 7c x+3 =

14 a m+ 2 − x m +3 − 5 + 8 − 3a m+ 2 + 5 x m +3 − 6 + a m + 2 − 5 x m +3 =

15 0.3a + 0.4b + 0.5c − 0.6a − 0.7b − 0.9c + 3a − 3b − 3c =

1 1 3 1 3 1
16 a + b + 2a − 3b − a − b + − =
2 3 4 6 4 2

3 2 1 1
17 m − 2mn + m 2 − mn + 2mn − 2m 2 =
5 10 3

3 1 5 1 3 1 1
18 − a 2 + ab − b 2 + 2 a 2 − ab + b 2 − b 2 − 2ab =
4 2 6 3 4 6 3

3 2 1
19 0.4 x 2 y + 31 + xy 2 − 0.6 y 3 − x 2 y − 0.2 xy 2 + y 3 − 6 =
8 5 4

3 m−1 7 m− 2 3 m−1 1 m− 2 1
20 a − b + a − b − 0.2a m−1 + b m− 2 =
25 50 5 25 5
RESPUESTAS

1 7a − 9b + 6a − 4b
(7a + 6a ) = 13a (− 9b − 4b ) = −13b
= 13a − 13b

2 a + b − c − b − c + 2c − a
a−a =0 b−b =0 − c − c + 2c = 0
=0

3 5 x − 11 y − 9 + 20 x − 1 − y
5 x + 20 x = 25 x − 11 y − y = −12 y − 9 − 1 = −10
= 25 x − 12 y − 10

4 − 6m + 8n + 5 − m − n − 6m − 11
− 6m − m − 6m = −13m 8n − n = 7 n 5 − 11 = −6
= −13m + 7 n − 6

5 − a + b + 2b − 2c + 3a + 2c − 3b
− a + 3a = 2a b + 2b − 3b = 0 − 2 c + 2c = 0
= 2a

6 − 81x + 19 y − 30 z + 6 y + 80 x + x − 25 y
− 81x + 80 x + x = 0 19 y + 6 y − 25 y = 0 − 30 z
= −30 z

7 15a 2 − 6ab − 8a 2 + 20 − 5ab − 31 + a 2 − ab
15a 2 − 8a 2 + a 2 = 8a 2 − 6ab − 5ab − ab = −12ab 20 − 31 = −11
= 8a − 12ab − 11
2

8 − 3a + 4b − 6a + 81b − 114b + 31a − a − b
− 3a − 6a + 31a − a = 21a 4b + 81b − 114b − b = −30b
= 21a − 30b

9 − 71a 3b − 84a 4b 2 + 50a 3b + 84a 4b 2 − 45a 3b + 18a 3b
− 71a 3b + 50a 3b − 45a 3b + 18a 3b = −48a 3b − 84a 4b 2 + 84a 4b 2 = 0
= −48a 3b

10 − a + b − c + 8 + 2a + 2b − 19 − 2c − 3a − 3 − 3b + 3c
− a + 2a − 3a = −2a b + 2b − 3b = 0 − c − 2c + 3c = 0 + 8 − 19 − 3 = −14
= −2a − 14

11 m 2 + 71mn − 14m 2 − 65mn + m3 − m 2 − 115m 2 + 6m3
m3 + 6m3 = 7 m3 m 2 − 14m 2 − m 2 − 115m 2 = −129m 2 71mn − 65mn = 6mn
= 7 m3 − 129m 2 + 6mn
12 x 4 y − x 3 y 2 + x 2 y − 8 x 4 y − x 2 y − 10 + x 3 y 2 − 7 x 3 y 2 − 9 + 21x 4 y − y 3 + 50
x 4 y − 8 x 4 y + 21x 4 y = 14 x 4 y − x 3 y 2 + x 3 y 2 − 7 x 3 y 2 = −7 x 3 y 2
x2 y − x2 y = 0 − y3 − 10 − 9 + 50 = 31
= 14 x 4 y − 7 x 3 y 2 − y 3 + 31

13 5a x +1 − 3b x + 2 − 8c x + 3 − 5a x +1 − 50 + 4b x + 2 − 65 − b x + 2 + 90 + c x + 3 + 7c x + 3
5a x +1 − 5a x +1 = 0 − 3b x + 2 + 4b x + 2 − b x + 2 = 0
− 8c x + 3 + c x + 3 + 7c x + 3 = 0 − 50 − 65 + 90 = −25
= −25

14 a m + 2 − x m + 3 − 5 + 8 − 3a m + 2 + 5 x m + 3 − 6 + a m + 2 − 5 x m + 3
a m + 2 − 3a m + 2 + a m + 2 = − a m + 2 − x m +3 + 5x m +3 − 5 x m+ 3 = − x m +3 − 5 + 8 − 6 = −3
= −a m + 2 − x m +3 − 3

15 0.3a + 0.4b + 0.5c − 0.6a − 0.7b − 0.9c + 3a − 3b − 3c
0.3a + −0.6a + 3a = 2.7 a 0.4b − 0.7b − 3b = −3.3b 0.5c − 0.9c − 3c = −3.4c
= 2.7a − 3.3b − 3.4c

1 1 3 1 3 1
16 a + b + 2a − 3b − a − b + −
2 3 4 6 4 2
1 3 2+8−3 7 1 1 2 − 18 − 1 17 3 1 3−2 1
a + 2a − a = a= a b − 3b − b = b=− b − = =
2 4 4 4 3 6 6 6 4 2 4 4
7 17 1
= a− b+
4 6 4

3 2 1 1
17 m − 2mn + m 2 − mn + 2mn − 2m 2
5 10 3
3 2 1 2 6 + 1 − 20 2 13 1 − 6 −1+ 6 1
m + m − 2m 2 = m = − m2 − 2mn − mn + 2mn = mn = − mn
5 10 10 10 3 3 3
13 1
= − m 2 − mn
10 3

3 1 5 1 3 1 1
18 − a 2 + ab − b 2 + 2 a 2 − ab + b 2 − b 2 − 2ab
4 2 6 3 4 6 3
3 1 − 9 + 28 2 19 2 1 3 2−3−8 9
− a2 + 2 a2 = a = a ab − ab − 2ab = ab = − ab
4 3 12 12 2 4 4 4
5 1 1 − 5 +1− 2 2 6
− b2 + b2 − b2 = b = − b 2 = −b 2
6 6 3 6 6
19 9
= a 2 − ab − b 2
12 4
3 2 1
19 0.4 x 2 y + 31 + xy 2 − 0.6 y 3 − x 2 y − 0.2 xy 2 + y 3 − 6
8 5 4
2 2−2 2 3 2 3 − 1.6 2 1.4 2
0.4 x 2 y − x 2 y = x y=0 xy − 0.2 xy 2 = xy = xy = 0.175 xy 2
5 5 8 8 8
1 − 2.4 + 1 3 − 1.4 3
− 0.6 y 3 + y 3 = y = y = −.035 y 3 31 − 6 = 25
4 4 4
= 0.175 xy 2 − .035 y 3 + 25

3 m−1 7 m− 2 3 m−1 1 m− 2 1
20 a − b + a − b − 0.2a m−1 + b m− 2 =
25 50 5 25 5
3 m −1 3 m −1 3 + 15 − 5 m −1 13 m −1
a + a − 0.2a m −1 = a = a
25 5 25 25
7 1 1 − 7 − 2 + 10 m − 2 1 m − 2
− b m −2 − bm − 2 + bm −2 = b = b
50 25 5 50 50
13 1
= a m −1 + b m − 2
25 50